Advances and Applications of Block Copolymers (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The most important class of polymers is block copolymers (BCPs) since they can be prepared through different methods and exhibit various properties combined with chemically different segments. The importance of block copolymers can be supported by the multitude of related manuscripts published daily, their use in practical applications in almost all areas, and novel discoveries based on BCPs in many aspects of life. This Special Issue focuses on various matters from different areas of block copolymer research, showing advances and applications in self-assembly, crystallization, synthesis, chemical modification, 3D printing, membranes, energy materials, nanotechnology, hybrid materials, micelles, order–disorder transition, and biomaterials.